2019
DOI: 10.1016/j.neuroimage.2018.09.065
|View full text |Cite
|
Sign up to set email alerts
|

BOLD mapping of human epileptic spikes recorded during simultaneous intracranial EEG-fMRI: The impact of automated spike classification

Abstract: ObjectivesSimultaneous intracranial EEG and functional MRI (icEEG-fMRI) can be used to map the haemodynamic (BOLD) changes associated with the generation of IEDs. Unlike scalp EEG-fMRI, in most patients who undergo icEEG-fMRI, IEDs recorded intracranially are numerous and show variability in terms of field amplitude and morphology. Therefore, visual marking can be highly subjective and time consuming. In this study, we applied an automated spike classification algorithm, Wave_clus (WC), to IEDs marked visually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Previous studies using icEEG-fMRI have shown BOLD changes related to IEDs and seizures (32,33,40,52,53). Comparison of visual and automated IED classification on icEEG (53) presented a more objective interpretation of icEEG, but there was no statistically significant difference in concordance of the BOLD maps for two IED classification techniques.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies using icEEG-fMRI have shown BOLD changes related to IEDs and seizures (32,33,40,52,53). Comparison of visual and automated IED classification on icEEG (53) presented a more objective interpretation of icEEG, but there was no statistically significant difference in concordance of the BOLD maps for two IED classification techniques.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies using icEEG-fMRI have shown BOLD changes related to IEDs and seizures ( 32 , 33 , 40 , 52 , 53 ). Comparison of visual and automated IED classification on icEEG ( 53 ) presented a more objective interpretation of icEEG, but there was no statistically significant difference in concordance of the BOLD maps for two IED classification techniques. The relationship of BOLD clusters in surgical resection volume and in remote brain areas for different IED classes has not been explored in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…We performed experiments to quantify the amount of heating induced in the immediate vicinity of a set of intracranial EEG electrodes by exposure to RF generated by a body transmit coil in a 1.5T MRI scanner. This work builds directly on our experience of acquiring concurrent icEEG-fMRI data using a quadrature head RF transmit coil in the MRI scanner (Vulliemoz et al, 2011;Chaudhary et al, 2016;Murta et al, 2016Murta et al, , 2017Ridley et al, 2017;Sharma et al, 2019) and in particular the safety tests that made it possible (Carmichael et al, 2008) and associated scanning protocol (Carmichael et al, 2012). This protocol contains prescriptions on the choice of RF transmit coil, MR sequence, and the type, connection and positioning of the EEG wires and equipment, and relies to a large degree on the use of a scanner bore foam insert on which the EEG system can be placed precisely and consistently.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial electroencephalography during functional magnetic resonance imaging (IcEEG-fMRI) has been used to map epileptic activities (Vulliemoz et al, 2011;Boucousis et al, 2012;Carmichael et al, 2012) with much greater sensitivity enabling more detailed, quantitative studies of interictal, preictal and ictal epileptogenic networks (Vulliemoz et al, 2011;Cunningham et al, 2012;Aghakhani et al, 2015;Beers et al, 2015;Chaudhary et al, 2016;Ridley et al, 2017;Sharma et al, 2019) and of neuronal events more generally (Murta et al, 2016(Murta et al, , 2017Saignavongs et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…11 Intracranial EEG (iEEG) provides greater sensitivity to and spatial discrimination of IED sources, but relies heavily on the choice of location for electrode implantation. 12 Further, despite the potential for simultaneous iEEG-fMRI to provide a more reliable localization of IEDrelated BOLD changes, studies performed to date [13][14][15][16][17][18][19][20][21][22][23] have revealed instances of complex patterns that are difficult to interpret and require qualitative consolidation with the other relevant clinical information (eg, ictal iEEG recordings) and their clinical relevance.…”
Section: Introductionmentioning
confidence: 99%